2020
DOI: 10.3201/eid2608.200681
|View full text |Cite
|
Sign up to set email alerts
|

Infectious SARS-CoV-2 in Feces of Patient with Severe COVID-19

Abstract: Severe acute respiratory syndrome coronavirus 2 was isolated from feces of a patient in China with coronavirus disease who died. Confirmation of infectious virus in feces affirms the potential for fecal–oral or fecal–respiratory transmission and warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
509
3
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 501 publications
(544 citation statements)
references
References 10 publications
19
509
3
13
Order By: Relevance
“…Zang et al 34 , upon being unable to recover infectious SARS-CoV-2 from RNA-positive human fecal samples, have argued that the virus is rapidly inactivated by simulated human colonic uid. This conclusion is not consistent, however, with the ndings of Xiao et al 32 or Zhang et al 33 , who were able to recover infectious SARS-CoV-2 from human feces reviewed in 35 , or with the reports of Liu et al 20 and Chan et al 21 that SARS-CoV-2 remains infectious for hours in human fecal suspensions. The conclusion is also not consistent with results obtained for other coronaviruses, such as SARS-CoV and MERS-CoV 35 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Zang et al 34 , upon being unable to recover infectious SARS-CoV-2 from RNA-positive human fecal samples, have argued that the virus is rapidly inactivated by simulated human colonic uid. This conclusion is not consistent, however, with the ndings of Xiao et al 32 or Zhang et al 33 , who were able to recover infectious SARS-CoV-2 from human feces reviewed in 35 , or with the reports of Liu et al 20 and Chan et al 21 that SARS-CoV-2 remains infectious for hours in human fecal suspensions. The conclusion is also not consistent with results obtained for other coronaviruses, such as SARS-CoV and MERS-CoV 35 .…”
Section: Discussionmentioning
confidence: 66%
“…The indirect transmission pathway, envisioned as a patient's bodily uids-HITES-hands-mucous membrane nexus, is supported by experimental transmission studies in animal models 28 and by the results of investigations of the contamination of HITES with SARS-CoV-2 RNA in healthcare settings 25,[29][30][31] . The detection of infectious SARS-CoV-2 in patient feces 32,33 , together with the data on survival of SARS-CoV-2 in fecal suspensions 20,21 , suggest that a fecal/oral or fecal/respiratory route of transmission is possible. Zang et al 34 , upon being unable to recover infectious SARS-CoV-2 from RNA-positive human fecal samples, have argued that the virus is rapidly inactivated by simulated human colonic uid.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that there may be other potential routes of transmission, such as exposure to SARS-CoV-2 that survive in community environment. Given that the infectious SARS-CoV-2 was found to be secreted through the human urinary system ( Sun et al, 2020 ) and intestinal tract ( Wang et al, 2020d ; Xiao et al, 2020b ; Zhou et al, 2020a ), and SARS-CoV-2 RNA was detected in wastewater worldwide ( Randazzo et al, 2020 ), many studies have suggested the possibility of wastewater transmission of COVID-19 disease ( Adelodun et al, 2020 ; Arslan et al, 2020 ; Foladori et al, 2020 ). However, the direct use of untreated excreta as a fertilizer and the flushing of excreta from open cesspools into the waters on rainy days might lead to serious water pollution, including the SARS-CoV-2 within human excreta.…”
Section: Resultsmentioning
confidence: 99%
“…Infectious SARS-CoV-2 has been found in human excreta samples of COVID-19 patient in many previous studies ( Sun et al, 2020 ; Wang et al, 2020d ; Xiao et al, 2020b ; Zhou et al, 2020a ), and the SARS-CoV-2 embedded in stool particles in septic tanks could escape from disinfection and slowly release into aqueous phase, behaving as a secondary source of SARS-CoV-2 and potentially contributing to its spread through drainage pipelines ( Zhang et al, 2020c ). Former study has found that particles (kaolin clay, humic acid powder, and activated sludge) <2 μm in diameter were large enough to protect viruses from 254-nm ultraviolet (UV) light ( Templeton et al, 2005 ), suggesting that the protection of fecal particles might make the survival of SARS-CoV-2 more easier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation